2020
DOI: 10.1111/1462-2920.15309
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genomic characterization of the ibuprofen‐degrading bacterium Sphingomonas strain MPO218

Abstract: Summary The presence of pharmaceutical compounds in waters and soils is of particular concern because these compounds can be biologically active, even at environmental concentrations. Most pharmaceutical contaminants result from inefficient removal of these compounds during wastewater treatment. Although microorganisms able to biodegrade pharmaceuticals compounds have been described, the isolation and characterization of new bacterial strains capable of degrading drugs remain important to improve the removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…To identify the genes affected by the transposons, we sequenced the DNA regions flanking the insertions. The results indicated that mutations were located in three main regions ( Table 1 ) as follows: (i) the noncolored mutants are affected in the ipf region previously described as necessary for IBU metabolism ( 15 , 16 ), which is located in pIBU218 (region III in Fig. 1 ); (ii) the dark mutants are affected in a region containing genes related to biodegradation of aromatic compounds and that is also located on pIBU218 ( 16 ) (region I in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…To identify the genes affected by the transposons, we sequenced the DNA regions flanking the insertions. The results indicated that mutations were located in three main regions ( Table 1 ) as follows: (i) the noncolored mutants are affected in the ipf region previously described as necessary for IBU metabolism ( 15 , 16 ), which is located in pIBU218 (region III in Fig. 1 ); (ii) the dark mutants are affected in a region containing genes related to biodegradation of aromatic compounds and that is also located on pIBU218 ( 16 ) (region I in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The results indicated that mutations were located in three main regions ( Table 1 ) as follows: (i) the noncolored mutants are affected in the ipf region previously described as necessary for IBU metabolism ( 15 , 16 ), which is located in pIBU218 (region III in Fig. 1 ); (ii) the dark mutants are affected in a region containing genes related to biodegradation of aromatic compounds and that is also located on pIBU218 ( 16 ) (region I in Fig. 1 ); and (iii) the leaky mutant is affected in a gene annotated as a beta subunit of a propionyl-CoA carboxylase carboxyl transferase, located on the MPO218 chromosome.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations